The The Influence of Using the Name "Abah" for Candidate Pairs in the 2024 Presidential Election Campaign: Pengaruh Pemberian Nama "Abah" kepada Pasangan Calon dalam Kampanye Pilpres 2024 - Mujahidin, Achmad Aflach; M, Jacky (Paradigma, 2026)
The 2024 presidential election in Indonesia shows interesting political dynamics, including the use of political language and symbols. One interesting phenomenon is the use of the name "Abah" given to Candidate Pair (candidate) number 1. This study aims to analyze the effect of giving the name "Abah" on people’s perceptions and support for candidate 1 in the context of the 2024 Presidential Election campaign. The theory used in this research is symbolic interactionism because many people think this name is a name that tends to be given by the Muslim community. The research method used is qualitative research with a content analysis approach and in-depth interviews. Data were obtained from campaign recordings, social media, and interviews with respondents who were directly involved in the 2024 presidential election campaign. The analysis was conducted to understand how the use of the name "Abah" influenced people’s perceptions and support for candidate 1. The results showed that the use of the name "Abah" had asignificant influence in increasing people’s political identification and emotional engagement with candidate 1. It was found that the use of the name "Abah" indirectly portrayed a figure who was respected, wise, and had strong authority, which then created a positive image for candidate 1. However, there are also findings that suggest that the overuse of the name "Abah" can cause controversy and division among the community.